Correction: Effects of the support on bifunctional one-step synthesis of methylal via methanol oxidation catalysed by Fe–Mo-based bifunctional catalysts. Issue 20 (29th September 2022) - Yuan, Meng; Tang, Ruiyuan; Sun, Xiangyu; Zhang, Zhimei; Tian, Yuanyu; Qiao, Yingyun
Abstract : Correction for 'Effects of the support on bifunctional one-step synthesis of methylal via methanol oxidation catalysed by Fe–Mo-based bifunctional catalysts' by Meng Yuan et al., Sustainable Energy Fuels, 2021, 5, 246–260, ; https://doi.org/10.1039/D0SE01194K .